The story of soy - Du Bois, Christine M., 1962- (Reaktion Books, 2018)
"The humble soybean is the world's most widely grown and most traded oilseed. And though found in everything from veggie burgers to cosmetics, breakfast cereals to plastics, soy is also a poorly understood crop often viewed in extreme terms--either as a superfood or a deadly poison. In this illuminating book, Christine M. Du Bois reveals soy's hugely significant role in human history as she traces the story of soy from its domestication in ancient Asia to the promise and peril ascribed to it in the twenty-first century. Traveling across the globe and through millennia, The Story of Soy includes a cast of fascinating characters as vast as the soy fields themselves--entities who've applauded, experimented with, or despised soy. From Neolithic villagers to Buddhist missionaries, European colonialists, Japanese soldiers, and Nazi strategists; from George Washington Carver to Henry Ford, Monsanto, and Greenpeace; from landless peasants to petroleum refiners, Du Bois explores soy subjects as diverse as its impact on international conflicts, its role in large-scale meat production and disaster relief, its troubling ecological impacts, and the nutritional controversies swirling around soy today. She also describes its genetic modification, the scandals and pirates involved in the international trade in soybeans, and the potential of soy as an intriguing renewable fuel. Featuring compelling historical and contemporary photographs, The Story of Soy is a potent reminder never to underestimate the importance of even the most unprepossessing sprout."--